Peran ulul albab dalam mendidik generasi berakhlak, berilmu, dan berwawasan luas di era modern islam - Siwi, Respati Mulia; Maziah, Sailan; Azizi, Gayo Hafid; Abdillah, Muhammad Raehan (Maliki Interdisciplinary Journal, 2025)
The importance of studying the role of Ulul Albab in Islamic education as an effort to shape a generation that is moral, knowledgeable, and broad-minded in the modern era. Ulul Albab, known as a wise figure in the Qur’an, represents individuals who possess a balance between intellectual, spiritual, and emotional intelligence. In Islamic education, the concept of Ulul Albab emphasizes not only the mastery of knowledge but also the formation of character and noble morals. The Ulul Albab generation is expected to think critically and reflectively in facing the challenges of the times while firmly upholding Islamic values as a moral foundation. This study analyzes how the concept of Ulul Albab can be applied in the Islamic education curriculum and learning strategies that integrate knowledge with spiritual values. In a modern era filled with complexity and rapid change, education based on the principles of Ulul Albab has the potential to produce a generation of Muslims who are not only academically intelligent but also capable of making positive contributions to society through critical and ethical thinking. Thus, the concept of Ulul Albab can serve as a foundation for the development of adaptive Islamic education, rooted in local wisdom, and relevant to global challenges.